2010
DOI: 10.1159/000295210
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes towards Prenatal Diagnostic Procedures among Pregnant Women in Greece

Abstract: Objective: To assess knowledge and attitudes towards prenatal diagnostic procedures among pregnant women living in Greece who underwent amniocentesis or chorionic villus sampling in relation to underlying demographic, lifestyle and medical history predictors. Method: 354 women, upon receiving the results, were interviewed in person. A structured questionnaire was answered based upon sociodemographic, educational, lifestyle and medical history variables, as well as questions pertaining to the women’s knowledge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
2
12
0
2
Order By: Relevance
“…Women of higher education level were over twofold more likely to attain a higher level of knowledge of prenatal diagnostic procedures (Kitsiou‐Tzeli et al . ). It is known that socio‐economic status can influence the families’ decision regarding prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Women of higher education level were over twofold more likely to attain a higher level of knowledge of prenatal diagnostic procedures (Kitsiou‐Tzeli et al . ). It is known that socio‐economic status can influence the families’ decision regarding prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to our study's results, Kitsiou‐Tzeli et al . () assessed knowledge about and attitudes towards prenatal diagnostic procedures among pregnant women ( n = 354) living in Greece. Women of higher education level were over twofold more likely to attain a higher level of knowledge of prenatal diagnostic procedures (Kitsiou‐Tzeli et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the awareness about these procedures is gradually increasing, studies have revealed that much needs to be done to improve the efficiency of prenatal counselling [1]. An important aspect of prenatal counselling is to provide the procedural details along with information on the anticipated pain associated with the procedures.…”
Section: Introductionmentioning
confidence: 99%
“…No simple correlation has been found between the change in technology to the changes in values and beliefs toward genetic testing and prenatal procedures. Some think that genetic testing is a great advance while others think it will cause troubles [4].…”
Section: Introductionmentioning
confidence: 99%